A School-Based Screening Tool for Adolescents With Low Motor Coordination Abilities. Issue 5 (October 2019) - Mahmoud, Wala; Delextrat, Anne; Esser, Patrick; Dawes, Helen
This study sought to select the most relevant test items from the Bruininks-Oseretsky Test of Motor Proficiency, Second Edition (BOTMP-2) and from a selection of health-related fitness tests for identifying school teenagers with poor motor coordination. The 241 participants in this study (144 boys, 97 girls aged 13–14 years old) were tested on the short form of the BOTMP-2 and on the following additional fitness tests: (a) seated medicine ball test, (b) broad jump, (c) handgrip strength, (d) alternate hand ball wall toss, (e) 10 × 5-meter agility shuttle run, and (f) Chester step test. We performed a factor analysis of participant scores on these various tasks and BOTMP-2 test items to reduce them to the least number of meaningful and useful items. Four factors explained 45% of the data variance: gross motor skills and power (including broad jump, hand ball toss, shuttle run, and sit-ups tests); fine motor skills (including copying star, following the maze and paper folding); core strength and balance (including push-ups, hopping, and balance beam); and general body strength (including medicine ball throw and handgrip). We conclude that an efficient school-based battery of test items to screen 13-14 year old adolescents for fitness and coordination should assess these four factors and might especially rely upon the broad jump, copying a star shape, hopping handgrip strength, aerobic fitness, and wall ball toss.